Drivers of variation in migration behavior for a linked population of long-distance migratory passerine. (10th September 2019) - Bennett, Ruth E; Rodewald, Amanda D; Rosenberg, Kenneth V; Chandler, Richard; Chavarria-Duriaux, Liliana; Gerwin, John A; King, David I; Larkin, Jeffery L
Abstract: Despite advances in tracking technologies, migration strategies remain poorly studied for many small-bodied passerines. Understanding variation within a migration strategy is important as variation impacts a population's resilience to environmental change. Timing, pathway, and stopovers vary based on intrinsic and extrinsic factors that impact individual migration decisions and capacity. Here, we studied drivers of variation in migration across a linked population of Golden-winged Warbler ( Vermivora chrysoptera ) using data from 37 light-level geolocators. We tested if behaviors vary in response to extrinsic factors: season, year, and proximity to a large geographic barrier—the Gulf of Mexico—and intrinsic factors: age and wing chord. Spring migration was nearly twice as fast as fall migration, with tightly correlated arrival and departure dates that were consistent among years, in contrast to no correlation or consistency in fall. This aligns with predictions for selection to minimize time spent migrating in spring and a relaxation of that pressure in fall. Twenty-nine birds staged for multiple days (mean: 7.5, SE: 0.6) in stopover habitats before crossing the Gulf of Mexico in spring, but 6 individuals overwintering closer to the Gulf coast forewent the stopover and completed migration 8 days faster. These findings suggest birds capable of crossing the Gulf without a stopover may experience a selective advantage by minimizing total migration time. After crossing the Gulf, individuals reduced travel speed and stopover duration, indicating constraints on movement differ before and after the barrier. Wing chord, but not age, positively predicted the total distance and duration of migration, and neither varied with timing, suggesting migration distance impacts morphology, but strategies do not vary with age. Ultimately, we find undescribed stopover locations south of the Gulf are important for most of the population, while high variation in migration behaviors suggest potential resilience to changing environmental conditions. Causantes de variación en el comportamiento migratorio para una población vinculada de un paseriforme migratorio de larga distancia